New triterpenoid saponins from the stem bark of Hallea ledermannii. (17th February 2023) - Kouamé Koffi, Jean-Michel; Akoua Yao-Kouassi, Philomène; Alabdul Magid, Abdulmagid; Louis Evariste Akissi, Zachée; Martinez, Agathe; Sayagh, Charlotte; Voutquenne-Nazabadioko, Laurence
Graphical abstract: Highlights: Twenty-three triterpenoid saponins were isolated from Hallea ledermannii . Nine saponins including five quinovic, three cinchonic and one pyrocinchonic acid glycosides were newly described. Sugar moieties were identified as 6-deoxy-d -allofuranose, 6-deoxy-d -allopyranose, d -glucose, d -fucose, d -quinovose, d- xylose and l -rhamnose. This is the first report of triterpenoid saponins from Hallea ledermannii. Abstract: Twenty-three triterpenoid saponins (1 –23 ) have been isolated from the aquoeus and ethyl acetate fractions of the stem bark of Hallea ledermannii . Among them, nine (1 –9 ) are newly described, some of them containes uncommun natural 6-deoxy-d -allofuranose, 6-deoxy-d -allopyranose, and 6-deoxy-d -pyranose as a sugar moiety. This is the first report of the isolation and structural elucidation of these compounds from H. ledermannii . The chemical structure of the compounds was determined using NMR and HRMS data.